2010
DOI: 10.1097/01.ogx.0000368146.03137.f7
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in Endometrial Polyps: A 12-Year Experience

Abstract: Information is lacking from prospective studies on the incidence and risk factors for postoperative nerve injury after routine gynecologic surgery. In 2 retrospective studies, the reported risk of nerve injury from major gynecologic oncologic procedures was estimated to be between 1.1% and 1.9%. This prospective cohort study evaluated the overall incidence and time course of pelvic nerve injury in a population of 616 female patients undergoing elective gynecologic surgery for benign and malignant conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
3
11
1
3
Order By: Relevance
“…The present study, which was consistent with previously published data by Baiocchi et al (16), did not demonstrate any statistically significant difference between asymptomatic and symptomatic patients with regard to the presence of benign polyps and preneoplastic or neoplastic lesions. A potential explanation for this may be associated with the early diagnosis of polyps using transvaginal ultrasound, which is able to detect small polyps and endometrial thickness before they begin to bleed.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present study, which was consistent with previously published data by Baiocchi et al (16), did not demonstrate any statistically significant difference between asymptomatic and symptomatic patients with regard to the presence of benign polyps and preneoplastic or neoplastic lesions. A potential explanation for this may be associated with the early diagnosis of polyps using transvaginal ultrasound, which is able to detect small polyps and endometrial thickness before they begin to bleed.…”
Section: Discussionsupporting
confidence: 83%
“…In previously published studies, advanced age (>60 years), menopausal status, HRT and AUB were observed to be risk factors for malignancy in women with EPs (4,7,(16)(17)(18)37). In the present study, an age of >60 years was significantly associated with the risk of malignant progression of EPs; however, none of the remaining clinical variables considered were found to demonstrate such an association.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These findings seem to be similar to those reported in previous studies in which malignancy rate was described to vary between 0.8 and 8 % [12,[19][20][21][22]. One study reported a high prevalence of hyperplasia without cytologic atypia (25.7 %) and a prevalence of hyperplasia with atypia (3.1 %), and it added that polyps represent a wide spectrum of alterations that range from normal endometrium to cancer [12].…”
Section: Resultssupporting
confidence: 77%
“…In a meta-analysis performed by Lee et al 9 , it was determined that malignant endometrial polyps were present in 0.8 to 8% of the patients, depending on the population studied and the methods used for diagnosis and resection [10][11][12][13][14][15][16][17] . In postmenopausal women, there is a direct relationship between the size of endometrial polyps and the existence of atypical hyperplasia and endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%